Power Allocation Based on Relay Location and PU Location for CR Network - Fengdie Chen; Shouyi Yang; Bing Ning; Guangping Li (Dianxin kexue)
A new transmission mechanism called direct and relay-aided transmissions based on inter group cooperation was proposed for the cognitive radio network.The performance of a single-relay system based on amplify-forward in the Rayleigh fading environment by considering the interference constraints and peak power constraints was analyzed.The impact of the relay node and the primary users（PU）location on power allocation and system throughout was investigated and the performance of the optimal power allocation（OPA）scheme and equal power allocation（EPA）scheme was compared.The result shows that the locations of relay node and PU are crucial to the system performance and the proposal optimum power allocation scheme significantly outperforms the equal power allocation scheme.The best performance was achieved when the relay is at an equal distance from the sender and the destination in EPA scheme or the relay is closer to the destination around in OPA scheme.